2014
DOI: 10.1002/ccd.25705
|View full text |Cite
|
Sign up to set email alerts
|

Influence of percutaneous mitral valve repair using the MitraClip® system on renal function in patients with severe mitral regurgitation

Abstract: Successful PMVR was associated with an improvement in renal function. The improvement in renal function was associated with the extent of MR reduction and pre-existing kidney dysfunction. Our data emphasize the relevance of PVMR to stabilize the cardiorenal axis in patients with severe MR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 10 publications
(9 reference statements)
0
12
0
Order By: Relevance
“…As renal insufficiency was the only non-cardiac comorbidity which was independently associated with 30-day outcome in our study, renal function should be closely monitored peri-and postinterventionally and the decision for MitraClip therapy should be made on an individual basis in patients who suffer from multiple noncardiac comorbidities with special emphasis on impaired renal function. However, recently, an observational study including 60 patients undergoing the percutaneous MVR showed that an effective MR reduction by 2-3 grades can acutely improve renal function, whereas lesser MR reduction was associated with worsening of renal function in patients with normal to mild renal insufficiency [20]. Hereby, improvement of renal function after effective MVR may be due to favorable acute hemodynamic effects of the procedure such as increase in stroke volume and reduction of pulmonary and right ventricular pressures.…”
Section: Discussionmentioning
confidence: 93%
“…As renal insufficiency was the only non-cardiac comorbidity which was independently associated with 30-day outcome in our study, renal function should be closely monitored peri-and postinterventionally and the decision for MitraClip therapy should be made on an individual basis in patients who suffer from multiple noncardiac comorbidities with special emphasis on impaired renal function. However, recently, an observational study including 60 patients undergoing the percutaneous MVR showed that an effective MR reduction by 2-3 grades can acutely improve renal function, whereas lesser MR reduction was associated with worsening of renal function in patients with normal to mild renal insufficiency [20]. Hereby, improvement of renal function after effective MVR may be due to favorable acute hemodynamic effects of the procedure such as increase in stroke volume and reduction of pulmonary and right ventricular pressures.…”
Section: Discussionmentioning
confidence: 93%
“…Heart failure patients are characterized by severe left ventricular dysfunction with intact valve leaflets leading to functional mitral regurgitation (FMR), which is associated with a poor overall prognosis [ 1 ]. Transcatheter mitral valve repair (TMVR) using the MitraClip ® system has become an additional, low-risk, successful treatment option [ 2 , 3 ], even for multimorbid patients suffering from diabetes, renal dysfunction, or anemia [ 4 6 ]. TMVR reduces the severity of mitral regurgitation (MR) and leads to reversed cardiac remodeling, increased ejection fraction, and improved functional status over time [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…This association likely reflects the failure of shock physiology to resolve despite improvement in MR following TMVr and the severity of initial hemodynamic compromise and associated multi‐organ injury. AKI has previously been associated with increased short‐ and long‐term mortality following TMVr, suggesting that identifying patients at risk of AKI and providing appropriate periprocedural hemodynamic monitoring and support is likely to enhance outcomes 33,34 . Small studies of MCS use in patients undergoing transcatheter aortic valve replacement have suggested that elective as compared to emergent or “bail‐out” MCS utilization may improve survival 35,36 .…”
Section: Discussionmentioning
confidence: 99%